Chapter 12. Onion, Leek, and Chive Production: VPH ch. 12, CV299/HS730, 6/2024 - Desaeger, Johan; Dittmar, Peter J.; Roberts , ¨Pamela; Martini , Xavier; Zhang, Shouan; Zotarelli, Lincoln (EDIS, 2024)
Chapter 12 of the Vegetable Production Handbook of Florida